Degradation of organic nitrogenous wastes by a soil streptomycete - De, S; Chandra, A L (Folia microbiologica, 1979)
A soil streptomycete degraded hair, silk, wool, feather and leather which were collected from solid wastes. The organism was identified taxonomically and designated Streptomyces sp. A956. It degraded leather to the maximum extent and solubilized 35.9% of the total nitrogen, 2.32 mg of glycine equivalent amino nitrogen could be obtained by degradation of 100 mg leather.
Keywords: Wool; dusík; vlna; peří; Hair; Refuse Disposal; Animals; Soil Microbiology; Nitrogen; zvířata; vlasy, chlupy; Feathers; půdní mikrobiologie; Streptomyces; Skin; kůže; odpadky - odstraňování